The Role Of Transformational Leadership And Organizational Culture On Company Raediness In Transformation at PT Telkom Indonesia Tbk Telkom Regional II Division - Yudiani, Raden Amanda; Zusnita Muizu, Wa Ode (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract The readiness of Telkom Regional II to undergo transformation remains suboptimal due to several factors. Issues include inadequate allocation of corporate resources to support transformation initiatives, insufficient technological infrastructure integration, and low employee enthusiasm. This research aims to examine the influence of transformational leadership and organizational culture on the organization's readiness for transformation, focusing on the telecommunications industry in Indonesia. The study used a quantitative methodology that included partial least squares (PLS) and structural equation modeling (SEM). Structured surveys were used to gather information from 120 Telkom Regional II workers. Convergent validity, discriminant validity, and reliability tests were used to assess the validity and reliability of the outer model. Hypothesis testing showed significant positive impacts: transformational leadership influence organizational readiness (path coefficient = 0.149, p = 0.005), and organizational culture influenced both transformational leadership (path coefficient = 0.345, p = 0.000) and organizational readiness (path coefficient = 0.718, p = 0.000). Findings highlight the importance of leadership integrity, cultural collaboration, and resource optimization. However, challenges such as employee resistance and insufficient digital skills persist. This study recommends regular leadership training, strategic resource investment, and cultural development initiatives. Future research could broaden the scope by including more variables and comparing organizational dynamics across sectors. Keywords: Organizational Culture, Organizational Readiness, Telecommunication Industry, Transformational Leadership, Structural Equation Modeling